SISTEM PREDIKSI JUMLAH KASUS COVID-19 DI JAKARTA MENGGUNAKAN METODE LINEAR REGRESSION - Wisnu Hatta Nugroho (2021)
Covid-19 was a respiratory illness both of higher and lower parts which has caused by virus or bacteria. This infection disease could be able to spread into whole parts of respiratory system and the body would get lost much oxygen. This condition would be fatal, even the death. Covid-19 has a kind of the contagious disease easily. Therefore, to protect a number of Covid-19 prediction system in DKI Jakarta it needed a system by using Linear method application a number of coivd-19 prediction system in Jakarta this method could be able to use as a media device to estimate new case based on Covid-19 case in DKI Jakarta province that were happened. In analyzed data all variable which have used, were a number of daily positive case, a number of daily patients which hospitalized, a number of daily self-isolation and a number of daily vaccination 1 and 2. The ordinary least square (OLS) use Kolmogorov-Smirnov test, Spearman Rank test, and Heteroscedasticity test. After the data passing whole test, then input those data into regression linear model. Finally, the result could be examined it accuracy by using Coefficient of Multiple Determination (R2) dan Adjusted Coefficient of Determination (adjusted R2). The result of model accuracy test with R Square showed that 93,9% independent variables can explain the dependent variables. That said the prediction model has accuracy near 94% and the rest 6% is another unknown variable.